Ginkgo extract EGb 761 shields from slowly accumulating neurodegenerative-like changes in a newly developed cell culture model induced by the combined action of low doses of antimycin A1 and 2-deoxy-D-glucose - Plaschke, Konstanze; Bergmann, Marion; Kopitz, Jürgen (Journal of neural transmission, 2011)
Different cell culture models were already used to analyze the molecular base of the neuroprotective activities of the Ginkgo biloba extract EGb 761(®) after a single or short-term application. In these previous studies cells were severely injured with agents that promptly induce fatal cellular damage, like vast oxidative stress or mitochondrial dysfunction, and the protective effects of EGb 761(®) on such acute damage were evaluated. Our present study aimed to test EGb 761(®) action in cell cultures, where cellular functions are only moderately impaired by a longer lasting, but relatively modest oxidative stress, reduction of mitochondrial function and reduced intracellular energy levels, thereby causing only slow occurence of cellular damage over a time period of 2 weeks. To this end we used neuroblastoma cells (SK-N-MC) that were treated with low doses of a combination of antimycin A1 and 2-deoxy-D: -glucose. Addition of EGb 761(®) to the culture medium efficiently shielded the cells from progressing injury by reduced ATP-levels, oxidized redox state, lipid peroxidation damage and oxidative damage of mitochondrial DNA. As a result the cells were protected from apoptotic death that was observed in cultures without EGb 761(®) after 2 weeks of damage occurence. This cell culture system characterizing moderate cellular stress will be applied in future studies to further investigate the mode of action of single EGb 761(®) compounds.
Gesehen am 21.12.2022